The internal morality of criminal law - Edwards, J; Yusari, T (Oxford University Press, 2023)
According to a popular picture, criminal law lives up to the demands of its internal morality when its norms have counterparts with the same content in morality—when it conforms to what we call the mirror principle. This article argues that the popular picture must be redrawn by relying on a second principle, which we call the instrumental principle. Criminal law conforms to the instrumental principle when the existence of its norms helps to prevent or ameliorate moral wrongdoing. Our argument is that the instrumental principle forms part of the internal morality of criminal law, and supplies a justification for criminal laws that depart from the mirror principle. We further suggest that criminal law’s internal morality is asymmetrical: though departures from the mirror principle are sometimes justified by the instrumental principle, departures from the latter are not justified by the former.